Effects of pericapsular nerve group block versus local anesthetic infiltration for postoperative analgesia in total hip arthroplasty: A protocol for systematic review and meta-analysis - Lingzhi Rong; Tangqi Qin; Shoujia Yu; Donghang Zhang; Yiyong Wei (PLoS ONE, 2025)
Introduction This protocol for a systematic review and meta-analysis aims to provide synthesized evidence to determine whether pericapsular nerve group (PENG) block is superior to local anesthetic infiltration in controlling postoperative pain in total hip arthroplasty. Methods and analysis PubMed, EMBASE, Web of science, and the Cochrane library will be systematically searched from their inception to December 30, 2024. Randomized controlled trials (RCTs) that compared the analgesic effects of PENG block with local anesthetic infiltration for total hip arthroplasty will be included. The time to first analgesics requirement (analgesia duration) will be the primary outcome. Secondary outcomes will include the postoperative analgesics consumption over 24 hours, visual analog scale (VAS) scores at rest and movement, and the incidence of adverse effects. Statistical analysis will be conducted by RevMan 5.4 software. Ethics and dissemination Ethical approval is not applicable. The results of this study will be publicly published. PROSPERO registration number CRD42024590888